Ontogenetic variability in the feeding ecology of the spiny dogfish (Squalus acanthias, Squalidae) in the Northern Adriatic Sea. - ARMENDARIZ ZUASTI, IBON (2023)
reserved Ecosystem-based fishery management can be a useful tool to sustainably exploit marine resources. Trophic web knowledge is key for the construction of the ecosystem models used in this type of management, for which diet information is essential. Sharks, as top predators, play an important role in marine trophic webs and should be among the main focuses of research. The spiny dogfish (Squalus acanthias) is one of the most important commercial shark species, including in the heavily exploited Northern Adriatic Sea. In this study, the stomach contents of 249 S. acanthias captured between 2018 and 2022 off the coast of Porto Levante, in the Northern Adriatic Sea, were analyzed. The general diet composition was described based on several indexes: the percent frequency of occurrence (%FO), percent abundance (%PN), percent weight (%PW) and index of relative importance (%IRI). Percent fullness (fullness%) was also calculated as a proxy of feeding intensity, as well as two diet breadth indexes: the Shannon-Weaver index (H’) and Pielou index (J’). Differences in the diet were tested between sexes and three maturity stages (immature, maturing and mature) using PERMANOVA. The within-group similarity and between-group dissimilarity were also calculated using SIMPER. S. acanthias had an average total length (TL) of 552.5 ± 135.9 mm. 67 different prey items were identified and summarized into 17 aggregated categories for the analysis. Preys were mostly demersal. Teleost fishes formed the bulk of the diet (%IRI = 46.97%), followed by crustaceans (22.62%) and molluscs (14.9%). Fullness% was relatively low and highly variable (2.92 ± 2.33%) and may suggest an intermittent feeding strategy. H’ and J’ were also low (0.27 ± 0.36 and 0.29 ± 0.38, respectively). No significant changes in the diet were found between sexes. The diet of immature and mature individuals was significantly different (p-value = 0.01) and suggested the occurrence of ontogenetic changes. Teleosts and cephalopods increased their importance as ...